Counseling and Values Metastudy: An Analysis of Publication Characteristics From 2000 to 2019. Issue 2 (1st October 2021) - Alder, Candice; Yu, Candice; Bardhoshi, Gerta; Erford, Bradley T.
Abstract : Articles published in Counseling and Values: Spirituality, Ethics, and Religion in Counseling ( CVJ ) from 2000 to 2019 were analyzed for trends over time related to author characteristics and article content. Women now (2015–2019) compose more than two thirds of lead authors, about 90% of first and all authors are primarily affiliated with universities, and 12% of first authors from 2015 to 2019 are domiciled internationally. CVJ significantly increased the proportion of research publications while maintaining consistent proportions across all coded research variables. Only about 10% of articles focused on ethics, whereas 28% focused on spiritual and religious topics.